Degree of Skin Barrier Disruption Affects Lipid Organization in Regenerated Stratum Corneum - Tineke Berkers; Dani Visscher; Gert S. Gooris; Joke A. Bouwstra (Medical Journals Sweden, 2018)
Previously, a skin barrier repair model was developed to examine the effect of formulations on the lipid properties of compromised skin. In this model, the lipid organization mimics that of several skin diseases with impaired skin barrier and less dense lateral lipid organization. In addition, parakeratosis was occasionally observed. The present study investigated whether the extent of initial barrier disruption affects lipid organization and parakeratosis in regenerated stratum corneum. After barrier disruption and stratum corneum regeneration the fraction of lipids adopting a less dense lateral organization gradually increased with increasing degree of barrier disruption. Only when 75% of the stratum corneum was removed, were parakeratosis and a change in lamellar organization observed. This demonstrates the possibility of using the skin barrier repair model to study the effects of formulations on compromised skin in which the presence of parakeratosis and lipid organization can be modified by the extent of barrier disruption.